Multilevel safety climate in the UK rail industry: A cross validation of the Zohar and Luria MSC scale. (December 2018) - Curcuruto, Matteo; Griffin, Mark A.; Kandola, Rajkiran; Morgan, James I.
Highlights: Safety climate is a recognized leading indicator of safety performance. A validation of Zohar and Luria's MSC scale is provided for the rail industry. EFA, CFA and nomological analyses are used to test the MSC factor structure. Safety communication and monitoring factors are identified at team level. The original OSC factor is negatively associated with self-report accident indices. Abstract: Despite a downward trend in injury rates in UK workplaces, accident occurrence remains an on-going issue for the rail workforce. Results from the RSSB annual survey reveal that there were 164 major injuries in 2016/17. Safety climate is defined as "shared perceptions with regard to safety policies, procedures and practices." Many studies have examined the positive effects of safety climate on safety performances by individuals, teams, organizations. Despite widespread attempts to measure safety climate, the validity of measurement tools has not been systematically tested in the rail industry. The primary goal of our research was to validate Zohar and Luria's (2005) Multilevel Safety Climate Scale in a sample of rail infrastructure workers (N = 528). A cross-validation strategy was adopted. Half of the data were used to conduct exploratory factor analysis (EFA), with the remaining data submitted to confirmative factor analysis (CFA). The statistical results reveal a three-factor structure with organizational safety climate (OSC), supervisor safety communication (SSC), supervisor safety monitoring (SSM). A nomological analysis showed that SSC and SSM presented distinct correlation patterns with other measures of relevance for safety, risk and health management. SSM was found more strongly related with variables such as: safety priorities; safety systems; reporting attitudes; safety compliance. On the other hand, SSC was mainly related with measures refereed to distinct forms of organizational support: supervisor support; peer support; support to change. Overall, our findings showed the validity of a multidimensional approach on the study of safety climate and safety supervision in the rail industry.